Cyclic behavior of concrete columns reinforced with partially unbonded hybrid. (15th January 2017) - Ibrahim, Adam I.; Wu, Gang; Sun, Zeyang; Cui, Haoran
Abstract: This paper presents experimental and numerical results of concrete columns reinforced by longitudinal steel basalt fiber reinforced polymer (FRP) composite bars (SBFCB) and lateral stirrups steel-wire basalt FRP (BFRP) composite stirrups (SWBFCS). The main parameter is the un-bonded length of the SBFCB and concrete in the column base. Both SBFCBs and SWBFCSs consisting of inner steel bars or wires hybrid with outer BFRP. The axial compressive loading test of concrete cylinders confined by SWBFCS demonstrated the effective confinement of this new kind of stirrup. Moreover, in this paper, the bond relationship between the concrete and the SBFCBs was measured in three bridge columns. One column was utilized as a reference, and the other two with un-bonded lengths of 150 mm and 300 mm, covering the plastic hinge region above the column base. The hysteretic behavior, energy dissipation capacity, residual displacements, and curvatures of the three columns were analyzed. The results show that the maximum load of the proposed specimen with a 300 mm un-bonded length is increased by 15.8%, and the residual displacement was 9% smaller than that of the of the control specimen because of the un-bond length between concrete and SBFCB.